Legal Perspective On The Legality Of A Company Or Agency In Conducting Business - Ade Onny Siagian; Ramlani Lina Sinaulan; Joko Sriwidodo (International Journal of Law and Society, 2025)
In a company, it will always be connected to third parties and want to protect the company that is run honestly ("te goeder trouw"), so the legality of a company is important in business activities. The legality of a company or business entity is the most important element, because legality is the identity that legalizes or validates a business entity so that it is recognized by the public. The legality of the company must be valid according to laws and regulations, where the company is protected or covered by various documents until it is legal in the eyes of the law. Forms of Company Legality There are several types of identities that legalize a business entity, including: company name, company brand, and trade business license. While the benefits of company legality are as a means of legal protection, a means of promotion, proof of compliance with the law, making it easier to get a project and facilitating business development. The large number of companies that are established without legalizing the company is very detrimental to other companies that run their business activities honestly.